Floricultural opportunities for Caribbean ACP countries: COLEACP report (COLEACP RungisFR, 1993)
Highlights the opportunities that are opening up for Caribbean ACP countries to export floricultural produce to European Community countries. The markets studied within the EC are France, Germany, Italy, Netherlands, and the United Kingdom.
Contents: v.1 Summary and market studies v.2 Summary and Caribbean production